Destiny of the Explanatory Psalter by Maximus the Greek (to the history of the development of Sts Cyril and Methodius`s tradition in Moscow) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The Explanatory Psalter [Tolkovaia Psaltyri] written by Maximus The Greek [Maksim Grekh] found itself on the periphery of the philological research. Its author`s falling into disgrace and being accused of heresy precluded the publication of the Explanatory Psalter. Published in 1897 the Explanatory Psalter shows the literary language of the 1st half of the XVIth century. It also manifests the author`s innovative approach to the translation of the Holy books which included normalization and russification of the Church Slavonic language. The manuscript presents ample opportunity for the comprehensive and thorough study of the literary language of its time.
Keywords: Maximus The Greek; The Explanatory Psalter; translation; the Church Slavonic language; normalization; russification